Symmetric and asymmetric thermo-induced buckling and postbuckling of rotating GPLRC annular plates rested on elastic foundation. (15th May 2022) - Yang, Yukang; Luo, Qing; Li, Ji-an; Dong, Youheng; Chen, Bo; Li, Yinghui
Abstract: Investigating the instability of annular plate which revolves on its axis in thermal environment is a valuable subject in vehicle engineering and aerospace industry, for instance, extending the service life of engine bearing. The symmetric and asymmetric buckling and postbuckling induced by the temperature rise of a rotating graphene-platelets-reinforced composite annular plate rested on Pasternak foundation are studied in present paper. Asymmetric deformation forms are captured by adopting the first-order shear deformation theory. Introducing von Kármán's nonlinearity ensures the accuracy of postbuckling equilibrium paths. Highly coupled governing equations are solved by using the differential quadrature method and postbuckling paths are traced by utilizing the pseudo-arclength continuation algorithm. Parametric studies are conducted to discuss the influences of the dispersion patterns, weight fraction, and dimensions of GPLs, annular plate sizes, elastic foundation, and rotation motion on buckling and postbuckling. Results indicate that the sequence in which symmetric and asymmetric buckling modes appear is inextricably linked to the radial wave number of buckling configuration. Both adding GPLs and adjusting the foundation parameters appropriately can improve the ability to resist symmetric and asymmetric deformation of annular plate. The effect of rotation motion shows a transitional change along with the temperature rise. Highlights: The sequence in which symmetric and asymmetric buckling modes appear is studied. The impact of rotation motion on buckling and postbuckling is investigated. The reinforcement of GPLs on annular plate is explored. Multi-fields coupled analyses of annular plate are conducted.